Investigating the Effects of Direct Instruction and Facilitating Discourse on Social and Cognitive Presence in Blended learning - Mohamed Shameem Adam; Junainah Abd Hamid; Ali Khatibi; S. M. Ferdous Azam (Online Learning)
Community of Inquiry—a theoretical framework that consists of three interrelated elements: teaching presence, social presence, and cognitive presence—has widely been used in online and blended learning as an instructional design model to create and sustain conditions that facilitate meaningful learning in a learning community. Teaching presence is often regarded as the most important element for developing and maintaining social and cognitive presence, and directing the community for purposeful learning. However, little is known about the effects of sub-dimension of teaching presence on social and cognitive presence. This study examined the effects of direct instructions and facilitating discourse of teaching presence on social and cognitive presence in blended learning. Data was gathered from 466 blended learning students in higher education using the Community of Inquiry Survey. Results from structural equation modelling revealed that social presence has (i) a full mediating effect in the relationship between direction instruction and cognitive presence, and (ii) a partial mediating effect on the relationship between facilitating discourse and cognitive presence. The finding contributes to a better understanding of the influence of direct instruction and facilitating discourse of teaching presence on social and cognitive presence.